Dampak Nomophobia Gadget Terhadap Hasil Belajar Siswa Di Smk Negeri 3 Halmahera Barat - Jainudin Hasim; Syarifuddin Adjam; Fitriana Ibrahim; Asnita Ode Samili (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the impact of gadget nomophobia on student learning outcomes. The research method used is qualitative research. Data collection techniques in this study are observation, interviews and documentation. The research subjects in this study were students of SMK Negeri 3 West Halmahera. Sources of data in this study consisted of primary data and secondary data. The validity of the data in this study is the triangulation of sources, researchers, theories, and methods. The results of this study indicate that the impact of gadget nomophoia on student learning outcomes decreases because students' dependence on gadgets is very high, causing students to study less and be lazy in doing assignments given by their teachers. This has an impact on low student learning achievement after getting to know gadgets.